Mechanical Characteristics of Fiber-Reinforced Flexible Pipe Subjected to Axial Tensile Load - Zhenwen Sun; Weiping Huang; Hailong Lu; Yufeng Bu; Yuanchao Yin; Shichao Wang; Yimeng Fan (Journal of Marine Science and Engineering, 2023)
Fiber-reinforced flexible pipes are subjected to large axial tension loads in deep-water applications, which may result in the excessive deformation of the pipes. Owing to the anisotropy of the composite materials, accurately describing the tensile behavior of these pipes is difficult. Theoretical, numerical, and experimental methods are employed in this study to investigate the mechanical characteristics of a glass fiber-reinforced unbonded flexible pipe under axial tensile loads. Based on the load–strain relationship of each pipe layer, analytical equations considering the effect of anisotropy and radial deformation are first proposed to calculate the axial tensile stiffness of the pipe. A detailed numerical model is established to simulate the tensile behavior of the pipe. A prototype test is performed on a 4500 mm long sample using a tensile testing machine. The leading roles of outer tensile reinforcement layers in axial tensile capacity are illustrated by the strain energy of the pipe layers obtained by the numerical model. Subsequently, a comparison analysis of the mean fiber direction strains of the selected sections are performed between numerical and experimental results, which validates the numerical model. Additionally, the stress distributions of different pipe layers are discussed based on the results of the numerical analysis. Finally, the comparison of axial tensile stiffness results validates the accuracy of the analytical model considering radial deformation. This study proposes effective theoretical and numerical models to predict the tensile behavior of a fiber-reinforced flexible pipe, which provides useful references for the design and structural analysis of these pipes.